Efek Sinergis Madu dan Air Kelapa terhadap Maskulinisasi, Daya Tetas, dan Tingkat Kelangsungan Hidup Larva Ikan Nila (Oreochromis niloticus) - Irwan Azis; Indra Cahyono (Jurnal Riset Diwa Bahari (JRDB), 2025)
This study investigates the synergistic effects of honey and coconut water as natural masculinization agents on Nile tilapia (Oreochromis niloticus) larvae. The experiment evaluated the impact of these natural substances on sex ratio, hatchability, growth performance, and survival rate. A total of four treatments were tested: honey (15 ml/L), coconut water (30%), a combination of both, and a control group. Results showed that the combination of honey and coconut water yielded the highest masculinization ratio (94%), significantly higher than the control group (53%). Additionally, the combination treatment also exhibited superior hatchability (77.5%) and growth performance compared to the other treatments. Survival rates were highest in the combination group (94.67%), followed by coconut water (88.67%), honey (87.33%), and control (73.67%). This study provides promising evidence that honey and coconut water can be used as sustainable, eco-friendly alternatives to synthetic hormones in tilapia aquaculture.